Overcoming barriers and understanding the psychological impact of timely pig euthanasia on Spanish-speaking swine caretakers in the United States - Lamino, Pablo; Ceme Vinces, Renzo; Acevedo León, Nancy F.; Boren-Alpízar, Amy; Schmidt, Marcelo; McGlone, John J.; Garcia, Arlene (Frontiers in Veterinary Science, 2025)
IntroductionThis study explores the complex experiences of Spanish-speaking swine caretakers with euthanasia, focusing on mental health, stress, burnout, and the impact of cultural factors.MethodsWe conducted qualitative focus groups with Spanish-speaking swine caretakers from multiple farms, gathering insights from individuals with varying levels of experience and cultural backgrounds. Data were analyzed using thematic analysis to identify key factors influencing the euthanasia process.ResultsThe study found that caretaker stress and burnout, exacerbated by the “caring-killing paradox,” significantly affect emotional wellbeing. Factors such as the frequency of euthanasia, level of knowledge and education, and cultural background were identified as influential. Caretakers performing euthanasia frequently showed signs of desensitization, while those with less experience experienced higher emotional distress. Cultural background influenced attitudes and decision-making regarding euthanasia.DiscussionThis research underscores the need for mental health support and culturally sensitive training programs for swine caretakers. The findings align with existing literature on occupational stress and burnout and highlight the importance of comprehensive support systems. Future research should further examine the psychological impact of euthanasia across diverse agricultural settings and develop targeted interventions to support caretakers' mental health and improve animal welfare practices.